Hierarchical medical system and local medical performance: A quasi-natural experiment evaluation in Shanghai, China - Liang, Chen; Zhao, Yihang; Yu, Chenglong; Sang, Peng; Yang, Long (Frontiers in Public Health, 2022)
Abstract Background: In order to maintain the order of social operation, it is necessary for medical departments providing high-quality and affordable medical services to local residents. It has been widely accepted in developed countries while the medical treatment systems in developing countries remain to be improved. This project intends to take hierarchical medical system pilot in Shanghai of China as an example to evaluate the policy effects of medical reform in developing countries. Methods and Results: By means of Differences-in-differences (DID) method, the causal relationship between medical care services improvement and hierarchical medical system implementation could be identified. This project also explores the differential effects of the policy intervention and confirms that policy pilot had significant improvement on medical performance in central districts while the result remains uncertain in terms of suburban districts. Furthermore, the dynamic effect of hierarchical medical system is also been identified with Event Study method, the policy pilot only had short-term effects towards local medical resources improvement. In order to figure out the function mechanisms of hierarchical medical system and explain why the policy pilot only had short-term effects, this project also conducts influencing mechanism analysis with Triple-differences (DDD) method. According to the empirical results, there is no direct evidence indicating the hierarchical medical system could bring obvious benefits from the perspectives of patients and medical institutions. Conclusions: For better implementation of hierarchical medical system in the future, long-term supervision mechanism should be attended more attention in the enforcement process of hierarchical medical system. At the same time, more safeguard measures should be both implemented such as supervising the charges condition of medical institution and conducting performance evaluation.